THE EFFECT OF CAPITAL STRUCTURE, PROFITABILITY AND CORPORATE GOVERNANCE ON COMPANY VALUE (Empirical Study on Manufacturing Companies in the Cosmetics and Household Goods Subsectors Listed on the IDX) - Ristati; Riska Yanti; Wardhiah; Nurlela (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to analyze the effect of capital structure, profitability, and corporate governance on firm value in cosmetics and household goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The method used is panel data regression analysis with a purposive sampling approach to 6 companies that meet the criteria for five years, resulting in a total of 30 observation data. The independent variables studied include Debt to Equity Ratio (DER) as a measure of capital structure, Return on Equity (ROE) as an indicator of profitability, and managerial ownership as a representation of corporate governance, while the dependent variable is Price Book Value (PBV) which reflects the value of the company. The results of the analysis show that capital structure (DER) has a positive and significant effect on firm value, Profitability (ROE) also shows a positive and significant effect on firm value, Conversely, corporate governance (KM), although important, does not show a significant effect on firm value in the context of this study. This study indicates the importance of managing capital structure and increasing profitability to increase firm value. These results are expected to provide insight for company management and investors in making strategic decisions.